2007
DOI: 10.1002/bdra.20399
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome of women exposed to azathioprine during pregnancy

Abstract: These results suggest that AZP (50-100 mg/day) does not triple the rate of birth defects; however, it is associated with lower birth weight, gestational age, and prematurity. Larger studies are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 29 publications
1
88
1
9
Order By: Relevance
“…Azathioprine is listed by the U.S. Food and Drug Administration as a category D drug, but it has been used in thousands of pregnant women. One recent study that compared 189 women exposed to azathioprine and 230 women not exposed found no difference in the frequency of congenital anomalies (28).…”
Section: Immunosuppressive Drugs In Pregnancymentioning
confidence: 96%
“…Azathioprine is listed by the U.S. Food and Drug Administration as a category D drug, but it has been used in thousands of pregnant women. One recent study that compared 189 women exposed to azathioprine and 230 women not exposed found no difference in the frequency of congenital anomalies (28).…”
Section: Immunosuppressive Drugs In Pregnancymentioning
confidence: 96%
“…A multicenter study found no difference in the fetal malformation rate between pregnancies exposed to azathioprine and unexposed pregnancies, but there was an association of azathioprine with lower birth weight, gestational age and prematurity [7]. Leukopenia and/or thrombocytopenia may occur in a proportion of neonates whose mothers took azathioprine throughout their pregnancies.…”
Section: Immunosuppression In Pregnant Women With Systemic Lupus Erytmentioning
confidence: 99%
“…AZA and 6-MP, both purine analogs, are pregnancy category "D" drugs, since gestational animal studies show a defined association with birth defects. Because of their cytotoxicity, and potential risk of birth defects, they should be used with great care during pregnancy [111] . Immunomodulators alter the activity of the immune system in order to decrease the body's inflammatory response and cause an overall immunosuppressive effect.…”
Section: -Mp/azamentioning
confidence: 99%
“…However, if there is a medical history of unexplained infertility or miscarriages, men should discontinue taking thiopurines at least four months before conception to improve fertility [114] . Conversely, Goldstein et al [111] studied 189 women who took AZA for different indications and later contacted a birth defects registry following delivery. That study failed to find a statistically significant increase in the rate of malformations (compared to 230 women who contacted the same service that were not on any potentially teratogenic treatment).…”
Section: -Mp/azamentioning
confidence: 99%